2016
DOI: 10.1002/acr.22686
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Followup of a Multicenter Cohort of 101 Patients With Eosinophilic Granulomatosis With Polyangiitis (Churg‐Strauss)

Abstract: Objective. To assess the long-term outcome in eosinophilic granulomatosis with polyangiitis (Churg-Strauss) (EGPA). Methods. A total of 101 patients fulfilling the American College of Rheumatology criteria for EGPA were included between 1990 and 2011. Clinical features, antineutrophil cytoplasm autoantibodies (ANCAs), and Five-Factors Score (FFS) were assessed at diagnosis. Overall and cumulative survival rates, relapse-free survival, and sequelae were studied based on ANCA status and FFS.Results. The rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 45 publications
2
57
2
5
Order By: Relevance
“…53 It is reported that 22.7% to 42.6% of patients with EGPA are positive for MPO-ANCAs or ANCAs. 2,[54][55][56][57][58][59][60] The prevalence of ANCAs in EGPA patients was less than that in microscopic polyangiitis or granulomatosis polyangiitis, such as ANCA-associated vasculitis. In the present study, there was no difference in serum IL-33 concentra- 27 In the present study, we had detected more CD4 + T cells producing IL-25 in peripheral blood in patients with EGPA at relapse than in those at remission or in patients with BA, although the difference was very small.…”
Section: Discussionmentioning
confidence: 97%
“…53 It is reported that 22.7% to 42.6% of patients with EGPA are positive for MPO-ANCAs or ANCAs. 2,[54][55][56][57][58][59][60] The prevalence of ANCAs in EGPA patients was less than that in microscopic polyangiitis or granulomatosis polyangiitis, such as ANCA-associated vasculitis. In the present study, there was no difference in serum IL-33 concentra- 27 In the present study, we had detected more CD4 + T cells producing IL-25 in peripheral blood in patients with EGPA at relapse than in those at remission or in patients with BA, although the difference was very small.…”
Section: Discussionmentioning
confidence: 97%
“…9,36 Head and neck manifestations are reported in 48%-96% cases at diagnosis. 37,38 Eosinophilia (>1.0 × 10 9 /L and/or >10% of leucocytes) develops subsequently, 39 which may be accompanied by fever. Whilst nasal crusting may occur in some cases, destructive features are typically absent.…”
Section: Eosinophilic Granulomatosis With Polyangiitismentioning
confidence: 99%
“…ANCA positive 31%-58% 26,37 MPO ANCA positive 25%-50% 26,47 ENT involvement 48%-96% 37,38 Rhinologic CRSwNP 42%-51% 37,38 Change in sense of smell 40% 47 Nasal crusting 8%-43% 47,48 Otologic OME/CHL 3%-12% 26 59 although the importance of abstinence from cocaine for a good outcome cannot be overstated.…”
Section: Prevalence Of Ent Features Of Eosinophilic Granulomatosis Wimentioning
confidence: 99%
“…Previous studies reported the different clinical patterns between ANCA‐positive and ANCA‐negative EGPA; kidney involvement and peripheral neuropathy are more frequently observed in patients with EGPA having ANCA than those not having ANCA . EGPA has relatively good prognosis in comparison with other systemic vasculitides: the overall remission rate reaches up to 93%; however, 20–30% of patients achieving remission may experience relapse . The overall mortality rate during long‐term follow‐up is approximately 10% of patients having experienced relapse …”
Section: Introductionmentioning
confidence: 99%
“…EGPA has relatively good prognosis in comparison with other systemic vasculitides: the overall remission rate reaches up to 93%; however, 20–30% of patients achieving remission may experience relapse . The overall mortality rate during long‐term follow‐up is approximately 10% of patients having experienced relapse …”
Section: Introductionmentioning
confidence: 99%